Analisis Rasio Likuiditas Perusahaan Daerah Air Minum (PDAM) Tirtasari Kota Binjai - Saharani, Dita; Saparuddin, Saparuddin (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the financial performance of PDAM Tirtasari Binjai using a liquidity ratio approach. This type of research is quantitative, which is a method of comparing company ratios from year to year which includes current ratios and fast ratios. The results of the company's liquidity analysis from 2015 to 2017, in general, can be said that the company's performance is not good enough. It can be seen from the fluctuations in the Current Ratio and Quick Ratio achieved by the company. The company's liquidity decreased due to short-term debt increasing greater than current assets. This is due to the company's bank loan maturing in December 2015 which resulted in the results of the current ratio analysis and the ratio fluctuating quickly.Â